Market orientation and performance: An empirical investigation in the retail industry in Greece - Panigyrakis, George G.; Theodoridis, Prokopis K. (My University, 2007)
Due to a void in the literature, the object of this study was to examine the adoption of market orientation and its impact on performance in a retail context. Supermarket chains with nation-wide stores in Greece were specifically selected. Findings clearly demonstrate a positive effect of market orientation on retail performance and support the notion that market orientation is an important determinant of firm performance. Retailers acknowledge the importance of implementing market orientation within their organizations. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Greece; Market orientation; Retail performance; Supermarket chains